Production of Pullulanase by Raoultella Planticola Dsmz 4617 Using Sago Starch as Carbon Source - Hii, Siew Ling (2006)
Production of pullulanase by Raoultella planticola DSMZ 46 17 was studied in batch fermentation using sago starch as a carbon source. The fermentations were carried out, firstly, in 500-mL Erlenmeyer flasks to search for a suitable cultivation medium for pullulanase production by this gram negative bacterium. For comparison, production of pullulanase by a locally isolated strain was also carried out. Secondly, further improvement of pullulanase production by R. planticola DSMZ 46 17 was done by using response surface methodology (RSM). The factors studied were sago starch, peptone and initial culture pH. The precise values of carbon-to-nitrogen (C/N) ratio that affect the pullulanase secretion by this gram-negative bacterium were also studied. Then, batch cultivations in 2-L stirred tank fermenter were carried out in an attempt to further improve pullulanase production by R. planticola DSMZ 461 7. Two important hydrodynamic parameters, i.e., aeration and agitation, were studied in detail. Unstructured model based on logistic and Luedeking-Piret equations were used to describe growth and pullulanase production by R. planticola DSMZ 4617 in both 500-mL shake flask and 2-L stirred tank ferrnenter. Cultivation of R. planticola DSMZ 4617 in modified mineral Czapek medium was found able to produce substantially high activity of pullulanase (320 times higher) as compared to 'Ohba-Ueda' medium. Among various carbon and nitrogen sources tested, sago starch and peptone were the best substrates for enzyme production, and under these conditions, R. planticola DSMZ 4617 produced 0.95 U/mL of pullulanase at initial culture pH around 7 and incubation temperature of 30°C. The partially purified pullulanase from R. planticola DSMZ 461 7 was optimally active at pH 6 to 7, and 50°C with stability ranges from pH 5 to 10. As compared with R. planticola DSMZ 4617, the local isolate B. cereus H1.5 was found to produce substantially high activity of protease during growth. This was the main reason that much of the pullulanase activity was lost during cultivation and partial purification processes and thus this local isolate is not appropriate for industrial applications. Therefore, the research work was focused on R. planticola DSMZ 4617. The RSM experiments based on central composite design (CCD) were found practical to derive a statisticai model for enhancement of pullulanase production by R. planticola DSMZ 4617. From this study, about 1.8-times of increment in pullulanase activity (1.70 U/mL) was achieved at 6.12 g/L sago starch, 15.34 g/L peptone and initial pH 7.23. Studies on C/N ratio hrther confirmed that the highest pullulanase production was obtained at ratio of 0.97 which correspondes to approximately 6.1 g/L of starch and 15.3 g/L peptone.The pullulanase productivity and yield were greatly influenced by the aeration and agitation conditions within the fennenter. High pullulanase activities in the fermenter were observed at aeration rate of 0.5 vvm and agitation speed of 250 rpm. Under this condition, the pullulanase production results were: pullulanase activity, 2.22 UImL; pullulanase productivity, 0.015 U/mLih and pullulanase yield, 369 U pullulanase g starch-'. Themodels proposed in this study fit significantly well to the experimental data with more than 95% confidence. This means that the proposed model can be used to explain growth and enzyme production at different chemical and physical conditions in a concise form which is comprehensible to those who wish to make use of the results. From the study, pullulanase production by R . - + + - .- _._ _ -+- . - -- - planticola DSMZ 4617 was found to be a non-growth associated process (a = O), where accumulation of pullulanase in the culture fluid occurred only during the nongrowth phase. An improved pullulanase fermentation process by R. planticola DSMZ 4617 has been successfully developed and it showed approximately 7-times increment of pullulanase production (2.22 UImL) in 2-L stirred tank fernenter with optimized medium composition and culture conditions as compared to cultivation employing original medium without optimized formulation in 500-mL shake flask (0.32 U/mL).